Genetic association between NFKB1 −94 ins/del ATTG Promoter Polymorphism and cancer risk: a meta-analysis of 42 case-control studies - Wang, Duan; Xie, Tianhang; Xu, Jin; Wang, Haoyang; Zeng, Weinan; Rao, Shuquan; Zhou, Kai; Pei, Fuxing; Zhou, Zongke (Scientific reports, 2016)
Accumulating evidences have indicated that the functional -94 ins/del ATTG polymorphism in the promoter region of human nuclear factor-kappa B1 ( NFKB1 ) gene may be associated with cancer risk. However, some studies yielded conflicting results. To clarify precise association, we performed a comprehensive meta-analysis of 42 case-control studies involving 43,000 subjects (18,222 cases and 24,778 controls). The overall results suggested that the -94 ins/del ATTG polymorphism had a decreased risk for cancer, reaching significant levels in five genetic models (dominant model: OR = 0.86, 95% CI = 0.79–0.95, P = 0.002; recessive model: OR = 0.84, 95% CI = 0.74–0.94, P = 0.003; homozygous model: OR = 0.77, 95% CI = 0.66–0.90, P = 0.001; heterozygous model: OR = 0.90, 95% CI = 0.83–0.98, P = 0.011; allelic model: OR = 0.89, 95% CI = 0.83–0.96, P = 0.002). Furthermore, the -94 ins/del ATTG polymorphism could confer a decreased or increased risk for cancer development among Asians and Caucasians, respectively. Additionally, the stratification analysis revealed a significant association between the variant and decreased risk of oral, ovarian and nasopharyngeal cancer in Asians. After we adjusted p values using the Benjamini-Hochberg false discovery rate method to account for multiple comparisons, these associations remained.